Information integration in electronic health information systems using service oriented architecture approach - Abu Bakar, Muhamad Shahbani; Ta'a, Azman; Hashim, Kamarul Faizal (Asian Research Publishing Network (ARPN), 2015)
Health Information System (HIS) integration constitutes one of the main challenges to the developers.Although current integration technologies are up to now quite mature, we confront several problems and challenges regarding the complexity of functions and database of the HIS.The efficiency and performance are the issues for the HIS implementation that related to information integration problems.This research proposed an approach using Service Oriented Architecture (SOA) through Web Services (WS) to integrate the information used by the HIS.This study explored the problems and issues of information integration in HIS and uses the WS and SOA to improve the performance of HIS.The performance of data integration is measured to evaluate the proposed approach.Moreover, benchmark with the current approach is carried out in order to describe the efficiency of the proposed solution.